Alfonso X of Castile-León : royal patronage, self-promotion and manuscripts in thirteenth-century Spain - Kennedy, Kristin (Church, faith, and culture in the Medieval West., 2019)
Today, the literary patronage of Alfonso X 'the Learned' of Castile (1252-1284) seems extraordinary for its time in the context of Europe. His cultural programme, which promoted his royal status and imperial ambitions, was hugely ambitious, and the paucity of information about the intellectual circumstances in which it took place magnifies the scope of Alfonso's achievements still further. This book argues that rather than providing a new cultural template for his kingdoms, Alfonso did little to promote institutional learning and preferred instead to direct the literary works he commissioned to a restricted, courtly audience who would understand the complex layers of symbolism in the representations of him that accompanied the texts. Despite this careful control, this book cites codicological and paleographical evidence to show that some codices traditionally ascribed to the royal scriptorium were copied at the behest of readers beyond the king's immediate circle.